Practical protocols for timed artificial insemination of jennies using cooled or frozen donkey semen. (19th January 2021) - Yang, Feng; Li, Nan; Liu, Bing; Yu, Jie; Wu, Shuaishuai; Zhang, Ruitao; Yang, Weigang; Ji, Chuanliang; Sun, Qianqian; Ma, Jinliang; Li, Min; Zhou, Jingqian; et al.
Abstract: Background: With the expansion of the donkey industry, timed artificial insemination (TAI) is becoming increasingly important in the reproductive management of jennies, however, TAI has not been widely investigated in donkeys. Objectives: To develop efficient TAI protocols for cooled or frozen semen in jennies, based around ovulation induction with a GnRH analogue. Study design: Experimental exploratory study. Methods and Results: In experiment 1, the effects of different GnRH analogue (deslorelin) doses, follicle diameter (FD) at induction, repeated use of a GnRH analogue, and the influence of season on induction efficiency, as well as distribution of ovulations over time after induction were investigated. Induction efficiency was sufficient with 2.2 mg deslorelin (≥90% ovulation within 48 hours of treatment). Ovulation rate between 24 and 48 hours was highest when the FD at treatment was 31‐35 mm, as compared to 25‐30 mm or 36‐40 mm. Repeated use of deslorelin or treatment during different seasons had no effect on induction efficiency. About 70% of ovulations occurred between 32 and 48 hours, and highest incidence of ovulation was at 36‐38 hours after induction. In experiment 2, TAI using cooled semen (1 × 10 9 motile sperm in a 10 mL volume) was performed once at 8 hours after induction ( n = 59). Pregnancy rate after TAI with cooled semen was 49.2% (29/59). In experiment 3, jennies were inseminated twice with 10 (n = 23), 5 (n = 31), 3 (n = 32), 2 (n = 82) and 1 (n = 66) straws (more than 50 × 10 6 motile spermatozoa in each 0.5 mL straw) of frozen semen at 34 and 42 hours after induction. The pregnancy rates were 30.4%, 35.5%, 34.4%, 29.3% and 28.8%, respectively ( P > 0.05). Main limitations: In the frozen semen trial, 22.5% (68/302) jennies were excluded after failure to ovulate during the appropriate time interval. In addition, there were no control groups for the AI trials. Conclusion: When FD reaches 31‐35 mm, a donkey jenny can be inseminated once using cooled semen at 8 hours or twice using frozen semen at 34 and 42 hours after deslorelin treatment. The frozen semen TAI protocol resulted in acceptable pregnancy rates using 1 × 10 8 motile spermatozoa per cycle.